2006
DOI: 10.1136/vr.159.10.314
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pigeon circovirus in cloacal swabs: implications for diagnosis, epidemiology and control

Abstract: Pigeon circovirus (picv) was detected in cloacal swab samples by means of a newly-developed, sensitive pcr. An initial investigation of 17 Belgian racing pigeons aged up to eight months showed that rates of detection of 88 per cent and above were achieved using samples of cloacal swab, blood and bursa of Fabricius. The sampling of 15 caged pigeons six times when they were from three to 31 weeks of age indicated that picv infections were more readily detected in cloacal swabs than in blood, and that the virus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…It is generally believed that hematological analyses do not have high diagnostic significance in pigeon circovirosis (10). Pathological lesions are often associated with secondary infections because of an immunosuppression induced by PiCV (10,(23)(24)(25), which corresponded with our results. Moreover, we observed lymphoid depletion in lymphatic organs (mainly bursa of Fabricious), follicular atrophy of the bursa of Fabricius and the presence of intracytoplasmic botryoid inclusions, which were considered pathognomonic for pigeon circovirus infection (24).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It is generally believed that hematological analyses do not have high diagnostic significance in pigeon circovirosis (10). Pathological lesions are often associated with secondary infections because of an immunosuppression induced by PiCV (10,(23)(24)(25), which corresponded with our results. Moreover, we observed lymphoid depletion in lymphatic organs (mainly bursa of Fabricious), follicular atrophy of the bursa of Fabricius and the presence of intracytoplasmic botryoid inclusions, which were considered pathognomonic for pigeon circovirus infection (24).…”
Section: Resultssupporting
confidence: 90%
“…1 year. According to the literature, PiCV poses the greatest threat for young pigeons, less than one year of age (16,25). Tavernier et al (23) reported the highest seasonal prevalence of PiCV infections between March and May.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirmed the importance of the excretion of PiCV in the droppings and explained the apparent ease with which this virus infection is propagated in the young pigeons not only within the dovecote but also between different dovecotes at the time of the first racing competitions. The detection of high virus DNA levels in cloacal swabs is also consistent with earlier results by Todd et al (2006), who showed*using a conventional PCR test*that PiCV DNA could be detected in the cloacal swabs from apparently healthy pigeons for long periods (up to 31 weeks) and from a small proportion of adult ( 1 year-old) pigeons. The detection of PiCV DNA in the serum from pigeon number 20, which was collected in 1991 in Belgium, was of interest given that PiCV infections were not diagnosed in Belgium prior to 1997 (Duchatel et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Circovirus infections in pigeons are diagnosed by performing molecular analyses of cloacal, blood and serum samples from live birds and samples of the BF and spleen from dead birds Todd et al 2002;Roy et al 2003;Franciosini et al 2005;Todd et al 2006;Freick et al 2008;Duchatel et al 2009). The isolation of PiCV genetic material from pigeons is not always indicative of a circovirosis due to the high prevalence of subclinical infections.…”
Section: Diagnosis Treatment and Preventionmentioning
confidence: 99%